Essential Oils as Modulators of TRPV1: A Scoping Review of Mechanisms and Preclinical Evidence for Natural Analgesics - Chaerul Fadly Mochtar; Andini Febriyanda; Andi Ainun Zulkiah Surur; Andi Sri Dewi Anggraeni; Ulfah Widyastuti Arsal; Nana Aulia Massakuta; Nita Magfirah Ilyas; Suriati (Journal of Basic Medical Veterinary, 2026)
Essential oils contain diverse bioactive constituents capable of modulating ion channels involved in nociception, including the transient receptor potential vanilloid 1 (TRPV1) channel. Increasing evidence suggests that these volatile compounds may exert analgesic effects through TRPV1-mediated mechanisms; however, findings remain scattered across heterogeneous preclinical studies. This scoping review aimed to systematically map the current evidence on how essential oils and their isolated constituents interact with TRPV1 in the context of pain modulation. A comprehensive search of PubMed, Scopus, and Web of Science (up to October 2025) was conducted using predefined keywords related to essential oils, TRPV1, and pain. Eligible studies included in vitro or in vivo experiments evaluating the activation, inhibition, or modulation of TRPV1 alongside pain-related outcomes. Twenty studies met the inclusion criteria and were extracted for authorship, experimental models, compound types, TRPV1-specific findings, and nociceptive effects. Results demonstrated three dominant mechanisms of TRPV1 modulation: (i) direct inhibition of TRPV1 activity by compounds such as linalyl acetate and α-humulene; (ii) agonist-induced activation followed by desensitisation, as observed with myrcene, carvone, and citral; and (iii) multi-target modulation in which TRPV1 interacts with additional TRP channels and inflammatory pathways. Across models of acute, inflammatory, and neuropathic pain, these mechanisms consistently produced significant antinociceptive effects. Overall, essential oils show strong potential as natural TRPV1-targeted analgesic candidates. However, methodological heterogeneity, limited mechanistic depth, and the lack of clinical validation remain key limitations.